214k views
3 votes
Please help and explain I have no idea what e and in meanssimplify this

Please help and explain I have no idea what e and in meanssimplify this-example-1
User Lying Dog
by
5.0k points

1 Answer

3 votes

Given


(e^(2-√(3)))^(2+√(3))

To simplify.

Step-by-step explanation:

It is given that,


(e^(2-√(3)))^(2+√(3))

Since


(a^x)^y=a^(xy)

That implies,


\begin{gathered} (e^(2-√(3)))^(2+√(3))=e^((2-√(3))(2+√(3))) \\ =e^(4-3) \\ =e^1 \\ =e \end{gathered}

Hence, the answer is e.

User Atams
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.